2018
DOI: 10.1155/2018/1928945
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Succinate Reduces Systemic ROS Production in Septic Rats, but It Does Not Reduce Creatinine Levels

Abstract: In sepsis, reactive oxygen species (ROS) production is increased. This process takes place mainly within the electron transport chain. ROS production is part of the pathophysiology of multiple organ failure in sepsis. Succinate yields Dihydroflavine-Adenine Dinucleotide (FADH2), which enters the chain through complex II, avoiding complex I, through which electrons are lost. The aim of this work is to determine if parenteral succinate reduces systemic ROS production and improves kidney function. Rats with cecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
1
12
1
3
Order By: Relevance
“…In contrast, parenteral succinate administered in rats that did not undergo cecal ligation and puncture does not cause any changes regarding the Control group, suggesting that succinate does not affect non-septic rats. In previous studies, it has been documented that succinate reduces serum ROS levels, but it does not improve creatinine levels in septic rats [22], but the present research aimed to nd a correlation between serum ROS levels and serum apoptosis markers, also, the correlation between apoptosis markers and organ dysfunction markers as bilirubin and creatinine.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, parenteral succinate administered in rats that did not undergo cecal ligation and puncture does not cause any changes regarding the Control group, suggesting that succinate does not affect non-septic rats. In previous studies, it has been documented that succinate reduces serum ROS levels, but it does not improve creatinine levels in septic rats [22], but the present research aimed to nd a correlation between serum ROS levels and serum apoptosis markers, also, the correlation between apoptosis markers and organ dysfunction markers as bilirubin and creatinine.…”
Section: Discussionmentioning
confidence: 88%
“…Different studies describe that succinate improved oxygen consumption in septic rat muscle [19], prolonged survival [20], and improved liver metabolic pro le [21]. In previous studies, it has been shown that succinate reduces ROS levels in septic rats [22].…”
Section: Introductionmentioning
confidence: 99%
“…The DCFH technique is an already described technique to measure intracellular ROS also in extracellular fluids [43][44][45][46]. It has been demonstrated in our laboratory that septic rats have higher levels of ROS than controls, and that the administration of parenteral succinate decreases ROS levels [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, arginine and proline metabolism is the core process of arginine, ornithine, proline, citrulline, and glutamate biosynthesis and metabolism [17]. Arginine is directly related to the production of nitric oxide in the body and participates in the regulation of end-stage renal degeneration [18-20]. In addition, the aminoacyl-tRNA biosynthesis pathway is related to oxidative stress, cell-cycle arrest, and apoptosis [21].…”
Section: Discussionmentioning
confidence: 99%